Code-Mixing on Instagram Captions Posted by the Fashion Influencer “AMELIA ELLE” - Wijaya, Dhiya Dzakirah (UNIB Press, 2022)
This research aimed to find out the types and the reasons for codemixing used by fashion influencer Amelia Elle on her Instagram captions. This research was a mixed-method. The subject of this research was Amelia Elle. The data in this research were features of code-mixing used by Amelia Elle, a fashion influencer, in her Instagram captions. The data source in this research is Instagram captions. In analyzing the data, the researchers only took the captions which contain code-mixing. The result of this research shows that Amelia Elle used a type of code-mixing most dominantly in her Instagram captions insertion. Based on the interview, co reason dominantly used is being emphatic about something. In conclusion types and reasons for code-mixing appears to be the personal interest of young Indonesian speakers.